Effects of cation substitution and temperature on the interaction between thermal barrier oxides and molten CMAS. Issue 2 (February 2015) - Poerschke, David L.; Levi, Carlos G.
Abstract The effectiveness of candidate rare earth (RE) bearing oxides to mitigate degradation of thermal barrier coatings by molten silicates is determined by the constitution and crystallization kinetics of the reaction products. The relationships between the oxide composition, test temperature, and reaction product constitution were investigated using sintered pellets of hafnates or zirconates containing YbO1.5, GdO1.5, or LaO1.5. The results suggest that the composition of the reprecipitated ZrO2- or HfO2-based phase, typically fluorite, is a useful indicator of the effectiveness of the silicate crystallization reactions. Meanwhile, the composition of the primary crystalline reaction product, typically a RE oxy-apatite, is relatively insensitive to the experimental variables considered herein. The observed trends indicate that the larger RE cations are more potent in rapidly crystallizing the silicate melt and that their relative effectiveness increases with the REO1.5 concentration in the coating material.